2019
DOI: 10.12784/nzcomjnl55.2019.3.20-26
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking engagement: Exploring women’s technology use during the perinatal period through a Kaupapa Māori consistent approach

Abstract: Background: Barriers to accessing perinatal health services in New Zealand remain a significant problem, especially for Māori and rural populations. Information technologies and telehealth can facilitate the distribution of health-related information and promote provider engagement during the perinatal period. Aim: This study explored the perceptions and use of technologies by women and their partners who were pregnant or new mothers/caregivers and who utilised Kaupapa Māori perinatal health services. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The overarching theme identified across all studies was connection between pregnant women and midwives. The ability to connect using technology enabled pregnant women to access healthcare services; thereby, it has reduced barriers to healthcare (Gasteiger et al, 2019;McCarthy et al, 2017). The use of communication technology, however, was not always viewed positively when it related to issues of privacy or where there were concerns with having the skills to access and use the technology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overarching theme identified across all studies was connection between pregnant women and midwives. The ability to connect using technology enabled pregnant women to access healthcare services; thereby, it has reduced barriers to healthcare (Gasteiger et al, 2019;McCarthy et al, 2017). The use of communication technology, however, was not always viewed positively when it related to issues of privacy or where there were concerns with having the skills to access and use the technology.…”
Section: Resultsmentioning
confidence: 99%
“…The use of communication technology, however, was not always viewed positively when it related to issues of privacy or where there were concerns with having the skills to access and use the technology. Three out of the five studies reviewed identified these issues as concerns (Dalton et al, 2014;Gasteiger et al, 2019;Shroder et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…for Māori patients, in gout management in primary care (Rolston et al, 2018), perinatal care (Gasteiger et al, 2019), and type 2 diabetes management via the Green Prescription programme (Williams et al, 2017). Our findings provide participant-centred evidence within community child health that can help inform the development of digital infrastructure such as applications to support healthy lifestyle programmes via health promotion and health literacy.…”
Section: Discussionmentioning
confidence: 99%